2013
DOI: 10.1128/jvi.01573-13
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Protein Kinase D Activation Mediates Respiratory Syncytial Virus-Induced Airway Barrier Disruption

Abstract: Understanding the regulation of airway epithelial barrier function is a new frontier in asthma and respiratory viral infections. Despite recent progress, little is known about how respiratory syncytial virus (RSV) acts at mucosal sites, and very little is known about its ability to influence airway epithelial barrier function. Here, we studied the effect of RSV infection on the airway epithelial barrier using model epithelia. 16HBE14o-bronchial epithelial cells were grown on Transwell inserts and infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 49 publications
7
101
0
Order By: Relevance
“…Previously, cortactin deficiency in mice had been demonstrated to affect mammalian zygotic development by modulating its association with actin filaments (Yu et al, 2010), but a role in cell-cell adhesion in mice had not been investigated. Different studies have attributed cortactin a role in epithelial (Rezaee et al, 2013;Zhao et al, 2012) and endothelial barrier functions (Dudek et al, 2004;Schnoor et al, 2011). However, wildtype PKD1-KI mice, in line with literature (Sinnett-Smith et al, 2011), did not display obvious physical phenotypes or alterations in tight junction proteins, such as claudin 1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, cortactin deficiency in mice had been demonstrated to affect mammalian zygotic development by modulating its association with actin filaments (Yu et al, 2010), but a role in cell-cell adhesion in mice had not been investigated. Different studies have attributed cortactin a role in epithelial (Rezaee et al, 2013;Zhao et al, 2012) and endothelial barrier functions (Dudek et al, 2004;Schnoor et al, 2011). However, wildtype PKD1-KI mice, in line with literature (Sinnett-Smith et al, 2011), did not display obvious physical phenotypes or alterations in tight junction proteins, such as claudin 1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In airway epithelial cells, it has been shown that the synthetic double-stranded RNA polyI:C induces PKD phosphorylation/activation and epithelial barrier disruption and that the epithelial barrier disruption by polyI:C could be attenuated by Gö6976, a selective inhibitor of PKD and classical PKC isoforms (35). Moreover, Rezaee et al (59) recently reported that airway epithelial barrier disruption induced by respiratory syncytial virus involved PKD-dependent actin cytoskeletal remodeling, possibly dependent on cortactin activation. These findings support a role of PKD in the regulation of airway epithelial barrier formation.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of environmental exposures implicated in airway epithelial barrier dysfunction include respiratory viruses (e.g. coxsackie virus, rhinovirus and respiratory syncytial virus 48-51 ), air pollution components (e.g. ozone and ambient particulate matter 52-54 ), cigarette smoke 55, 56 , and allergens (considered below).…”
Section: Models Of Inducible Barrier Dysfunctionmentioning
confidence: 99%